Із сузір’я друзів: Звитяжці Кобилки-Сидоренки (матеріали до майбутньої енциклопедії Лесі Українки) - Диба, Алла; Dyba, Alla (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті представлено матеріали до біографій знайомих родини Лесі Українки Наталії Павлівни і Гаврила Романовича Сидоренків та їхніх нащадків, які складають інтелектуальну еліту України. Опубліковані тут документальні джерела можуть бути використані для написання статей до енциклопедії Лесі Українки. Article submissions to the friends’ biographies of Lesya Ukrainka’s family Natalia Pavlivna and Gavrylo Romanovуch Sуdorenko and their descendants that make up the intelectual elite of Ukraine. Particular attention is paid to the study of friendship and cooperation of N. P. Kobylko-Sуdorenko with O. P. Kosach-Kryvynіuk and stored and later transferred to Kyiv Museum of Lesіa Ukrainka memorialm things of Kosach’s family. Published here documentary sources can be used to write articles for the Encyclopedia of Lesіa Ukrainka.
From the Constellation of Friends: Winners Kobylky-Sуdorenky (Materials for the Forthcoming Encyclopedia of Lesіa Ukrainka)
Keywords: дисертація; бібліотекар-референт; фармаколог; офтальмолог; фтизіатр; інфекціоніст; клітинна біологія; біотехнологія рослин; пташиний грип; генетика; dissertation; librarian assistant; pharmacologist; oftalmologist; phtisiologist; infectious disease; cell biology; plant biotechnology; avian influenza; genetics